1981
DOI: 10.1152/jappl.1981.50.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of the chest wall and occlusion pressures in awake humans

Abstract: During CO2 rebreathing in sitting position seven of nine conscious men showed a progressive fall in expiratory reserve volume, most of it due to a decrease in abdominal volume. Diaphragm length at end expiration was thus increased, and some elastic recoil pressure became available to drive inspiration. In four out of six subjects, when CO2 tension was greater than 55 Torr, there was a dip in abdominal pressure at the beginning of inspiration, and the change in transdiaphragmatic pressure during the first 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 0 publications
3
26
1
Order By: Relevance
“…The present finding of a gradual decrease in VAbd,EE are in line with results obtained by magnetometry or respiratory inductance plethysmography in healthy subjects [10,19,[25][26][27][28] and patients with ankylosing spondylitis [4]. The novel finding of the present study, in which a method that neither requires calibration nor depends on the degree of freedom was used [16], was the direct assessment of volume changes in the three chest wall compartments.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present finding of a gradual decrease in VAbd,EE are in line with results obtained by magnetometry or respiratory inductance plethysmography in healthy subjects [10,19,[25][26][27][28] and patients with ankylosing spondylitis [4]. The novel finding of the present study, in which a method that neither requires calibration nor depends on the degree of freedom was used [16], was the direct assessment of volume changes in the three chest wall compartments.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
“…Respiratory muscle recruitment during hypercapnic stimulation has long been assessed in healthy humans [18, 26-28, 30, 31]. Some of these studies have shown that a decrease in the VAbd,EE optimises diaphragm configuration so that it can generate more pressure [26][27][28]. A novel finding of the present study is the direct assessment of PM,rc,I and PM,rc,E, PM,Abd and pressure production by the diaphragm in patients with ankylosing spondylitis.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Since the rate of CO2 elimination is directly proportional to 14, it seems appropriate that 1I would be maintained in the face of rising P., co regardless of body position. Our data and that from other investigators (Rigg et al 1974;Grassino, Derenne, Almirall, Milic-Emili & Whitelaw, 1981;Chapman & Rebuck, 1984a;Xie et al 1991) are consistent in this regard. In the present study, however, it was demonstrated that higher peak APOeS I was developed in order to maintain the same VT and P4 in the supine as in the upright position.…”
Section: Subjectssupporting
confidence: 92%
“…Second, the reduced EELV means that the diaphragm is lengthened, enabling this muscle to operate near its optimal length for force generation (101,114). Third, the reduced EELV allows for storage of elastic energy in the chest and abdominal walls during expiration that can be used to produce a portion of the work required during the ensuing inspiration (5, 35), although it is also possible that inspiration is aided in this situation by passive descent of the diaphragm (35). Importantly, accessory respiratory muscles are progressively recruited with increasing ventilatory demand during exercise, thereby sharing the load needed to support the exercise hyperpnea (6).…”
Section: Exercise Demands On the Respiratory Musclesmentioning
confidence: 99%